The Impact of Customer Experience and Customer Engagement on Behavioral Intentions: Does Competitive Choices Matters? - Ahmed, Bilal; Zada, Shagufta; Zhang, Liang; Sidiki, Shehla Najib; Contreras-Barraza, Nicolás; Vega-Muñoz, Alejandro; Salazar-Sepúlveda, Guido (Frontiers in Psychology, 2022)
The study aims to analyze behavioral intentions influenced by customer engagement, experience, and identification moderated by competitive choices in the granite sector of Pakistan. The study has been carried out through primary data analysis of cross- sectional approach in the transition to a sustainable economy. Four hundred questionnaires were distributed, for which only 216 were filled and usable with a response rate of 54%. Data was collected from Production managers and units, whereas missed mine holders and labor. Analyzed the data in SPSS and AMOS to run various tests, i.e., reliability, correlation analysis, regression, moderation regression, and confirmatory factor analysis. The study findings indicate a positive and significant relationship and effect among the variables. The reviews might contain some biases. Therefore, this study recommended adopting a probability sampling technique for future studies. The study results in a positive manner indicating customer service involvement as a significant factor in behavioral intention despite competitive options.